Reduced graphene oxide-supported hollow Co3O4@N-doped porous carbon as peroxymonosulfate activator for sulfamethoxazole degradation - Chen, Yanling; Bai, Xue; Ji, Yetong; Shen, Ting (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
•A novel hollow Co3O4@NPC/rGO composite was synthesized.•Complete removal of SMX by Co3O4@NPC/rGO/PMS system was achieved within 5 min.•The ROS contributions in bulk solution and on catalyst surface were first calculated.•Co sites, CO and N doping sites contributed to the excellent catalytic activity.•Ecotoxicity, reusability, stability and application potential were evaluated. A novel reduced graphene oxide-supported hollow Co3O4@N-doped porous carbon (Co3O4@NPC/rGO) composite was synthesized via self-assembly and pyrolysis-oxidation using bimetallic zeolite imidazolate frameworks and graphene oxide as precursors. The as-obtained composite exhibited superior performance on peroxymonosulfate (PMS) activation over a wide pH range. Complete removal of sulfamethoxazole (SMX, 25 mg·L−1) was achieved within 5 min and the reaction rate constant was higher than those of the most reported heterogeneous catalyst/PMS systems for SMX degradation. It was demonstrated that both radical pathways (SO4−, OH, and O2−) and non-radical pathways (1O2 and direct electron transfer) were involved in the SMX degradation. Significantly, the contribution ratio of each reactive oxidative species (ROS) in the bulk solution or on the catalyst surface was differentiated and calculated for the first time. SO4− both in the bulk solution and on the catalyst surface as well as the 1O2 in the bulk solution were the dominant ROS. The possible degradation mechanism of SMX by Co3O4@NPC/rGO/PMS system was proposed. Co active sites with high activity, the electron-rich ketonic group and the nitrogen doping sites within Co3O4@NPC/rGO contributed to the excellent catalytic activity. The ecotoxicity of SMX and its intermediates was investigated. Besides, the reusability, stability and application potential in actual waterbodies of Co3O4@NPC/rGO were evaluated. Overall, this work expands the environmental application of metal–organic frameworks (MOFs)-derived hollow nanomaterials and provides a promising heterogeneous catalyst for the elimination of refractory contaminants by sulfate radical-based advanced oxidation processes (SR-AOPs).